Central role of RIPK1-VDAC1 pathway on cardiac impairment in a non-human primate model of rheumatoid arthritis. (December 2018) - Zeng, Fanxin; Wen, Wei; Cui, Weiyi; Zheng, Wen; Liu, Yuli; Sun, Xueting; Hou, Ning; Ma, Dongwei; Yuan, Ye; Shi, Huiping; Wang, Zhimin; Li, Zezhong; et al.
Abstract: Rheumatoid arthritis (RA) is a chronic inflammatory disorder characterized by destructive polyarthritis and systemic complications. It increases cardiovascular morbidity and mortality. However, the mechanism underlying RA-related cardiac damage remains largely unknown. Here, we found and characterized a non-human primate (NHP) model with spontaneous RA similar to the human conditions. Compared with the control group, the cardiac function in RA monkeys showed progressively deterioration; histologically, we found significantly increased inflammatory cell infiltration, cell death, and fibrosis in RA monkey heart tissue. Mechanistically, the upregulated receptor-interacting protein kinase 1 (RIPK1) in RA monkey heart tissue bound to voltage-dependent anion-selective channel 1 (VDAC1), increased VDAC1 oligomerization, and subsequently induced cardiac cell death and functional impairment. These findings identified that RIPK1-VDAC1 pathway is a promising target to treat cardiac impairment in RA. This unique model of RA will provide a valuable tool for mechanistic and translational studies. Highlights: RA monkeys show sustained systemic inflammation and progressive deterioration of cardiac systolic function. Cardiac cell death, inflammatory cell infiltration and fibrosis are increased in RA monkey heart tissues. RIPK1, Caspase-8 and VDAC1 expression and their complex formation are upregulated in RA monkey hearts. RIPK1 promotes VDAC1 oligomerization, and subsequently induces cardiac cell death. RIPK1 D324 site is important for VDAC1 oligomerization.